Effects of weight assisted dry-land strength training on swimming performance - Trappe, S. W.; Pearson, D. R. (The Journal of Strength and Conditioning Research, 1994)
To compare the effects of 6 weeks of weight assisted training (WAT) to free-weight training on swimming performance, 10 highly trained collegiate swimmers were performance matched and divided into two equal groups (n=5). Both groups swam together during the 12-week study. The only difference between the groups was the mode of strength training. No significant differences were observed between groups in power gains as measured by tethered swimming and a biokinetic swim bench. However, the WAT group did show a significant improvement in swim bench power. Performance measures in a 22.9-m and 365-m front crawl time revealed no variation between groups at any measured time points. From baseline to Week 12 the WAT group improved significantly in the 22.9-m front crawl sprint. Both groups significantly decreased their 365.8-m time by approximately 4% from Weeks 4 to 12. No observed changes occurred in stroke rate or distance per stroke. These data suggest that weight assisted training did not provide an advantage as compared to free-weight training, or a disadvantage when applied to front crawl swimming.